The ammonoids from the Gattendorfia Limestone of Oberrödinghausen (Early Carboniferous; Rhenish Mountains, Germany) - Korn, Dieter; Weyer, Dieter (European Journal of Taxonomy, 2023)
The railway cutting near Oberrödinghausen at the northern margin of the Rhenish Mountains is the cardinal section for the investigation of Early Tournaisian (Early Carboniferous; Mississippian) ammonoids. The ammonoids from the Hangenberg Limestone (= Gattendorfia Limestone) of this and neighbouring outcrops are revised here, using the historical collections as well as undescribed new material. The ammonoid assemblages are composed of a total of 67 species, which occur in four successive ammonoid zones. The assemblages are composed of predominant prionoceratids (Order Goniatitina) with the twenty genera Mimimitoceras (two species), Globimitoceras (one species), Paragattendorfia (two species), Kornia (three species), Stockumites (eleven species), Acutimitoceras (two species), Costimitoceras (one species), Nicimitoceras (four species), Imitoceras (one species), Voehringerites (one species), Gattendorfia (eight species), Zadelsdorfia (two species), Kazakhstania (one species), Gattenpleura (one species), Weyerella (three species), Hasselbachia (three species), Paprothites (five species), Pseudarietites (three species), Rodingites (two species), Paralytoceras (one species) as well as subordinate eocanitids (Order Prolecanitida) with the genera Eocanites (eight species) and Nomismocanites (one species). The new genera Rodingites gen. nov. and Nomismocanites gen. nov. as well as the new species Mimimitoceras perditum sp. nov., Kornia fibula sp. nov., Kornia acia sp. nov., Stockumites parallelus sp. nov., Stockumites voehringeri sp. nov., Acutimitoceras ucatum sp. nov., Acutimitoceras paracutum sp. nov., Imitoceras initium sp. nov., Gattendorfia rhenana sp. nov., Gattendorfia bella sp. nov., Gattendorfia valdevoluta sp. nov., Gattendorfia schmidti sp. nov., Gattendorfia corpulenta sp. nov., Gattendorfia immodica sp. nov., Zadelsdorfia oblita sp. nov., Weyerella lenis sp. nov., Hasselbachia erronea sp. nov., Paprothites beckeri sp. nov., Paprothites kullmanni sp. nov., Eocanites delicatus sp. nov. and Nomismocanites raritas gen. et sp. nov. are described from Oberrödinghausen. Mimimitoceras mina sp. nov., Stockumites marocensis sp. nov., Zadelsdorfia zana sp. nov. and Kazakhstania kana sp. nov. are newly named for material from the Anti-Atlas of Morocco.